Comorbidity in social anxiety disorder: diagnostic and therapeutic challenges - Ahmet Koyuncu; Ezgi İnce; Erhan Ertekin; Raşit Tükel (BioExcel Publishing Ltd, 2019)
Comorbid disorders are highly prevalent in patients with social anxiety disorder, occurring in as many as 90% of patients. The presence of comorbidity may affect the course of the disease in several ways such as comorbidity in patients with social anxiety disorder (SAD) is related to earlier treatment-seeking behavior, increased symptom severity, treatment resistance and decreased functioning. Moreover, comorbidities cause significant difficulties in nosology and diagnosis, and may cause treatment challenges. In this review, major psychiatric comorbidities that can be encountered over the course of SAD as well as comorbidity associated diagnostic and therapeutic challenges will be discussed.